2021
DOI: 10.3390/catal11040511
|View full text |Cite
|
Sign up to set email alerts
|

Do Gas Nanobubbles Enhance Aqueous Photocatalysis? Experiment and Analysis of Mechanism

Abstract: The performance of photocatalytic advanced oxidation must be improved in order for the technology to make the jump from academic research to widespread use. Research is needed on the factors that cause photocatalysis to become self-limiting. In this study, we introduced, for the first time, nanobubbles continuously into a running photocatalytic reactor. Synthetic air, O2, and N2 bubbles in the size range of 40 to 700 nm were added to a reaction system comprising P25 TiO2 photocatalyst in stirred aqueous soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 51 publications
0
0
0
Order By: Relevance
“…Also, researchers Fan et al [89] implemented nanobubbles with a size of 1.08 ± 0.37 µm in their study, with an efficiency of 41-141% higher than that of conventional bubbles in the hole oxidation of H 2 O on TiO 2 . In both studies, the effect of medium pH on nanobubble size was demonstrated [90].…”
mentioning
confidence: 93%
“…Also, researchers Fan et al [89] implemented nanobubbles with a size of 1.08 ± 0.37 µm in their study, with an efficiency of 41-141% higher than that of conventional bubbles in the hole oxidation of H 2 O on TiO 2 . In both studies, the effect of medium pH on nanobubble size was demonstrated [90].…”
mentioning
confidence: 93%